Lack of evidence for a consistent differential impact of tail and tunnel handling on markers of welfare in laboratory mice - Neele Meyer; Rebekka Gottschalk; Lena Jakobi; Anna-Maria Schönhoff; Chadi Touma (Scientific Reports)
Abstract Different handling methods for laboratory mice have been intensely debated in light of refining animal husbandry. Several studies claim that tail handling is aversive, while tunnel handling seems to have a lesser impact on animal welfare. However, most of these studies investigated the effect of handling performed in an unusually high frequency and prolonged duration, not matching laboratory routines. Therefore, the aim of our study was to investigate the impact of weekly cage change using tail versus tunnel handling on male and female C57BL/6J and CD-1 mice. Locomotion and exploratory activity as well as anxiety-related behaviour were measured. Moreover, the animals’ interest in social partners and social novelty as well as voluntary interaction with the handler were assessed. Reactivity and repeated activation of the HPA axis were monitored using corticosterone levels and adrenal gland and thymus weights. Only very few of the measured behavioural and stress physiological parameters differed significantly between the two handling groups, with varying direction. Our comprehensive analysis could thus reveal no consistent evidence supporting the superiority of one method over the other in terms of welfare of the handled mice.